Secondary School Workshop About Dynamics Supported by Computer Software - Szíki, Gusztáv Áron (International Journal of Engineering and Management Sciences, 2018)
In the framework of the “Debrecen Venture Catapult Program (EFOP-3.6.1-16-2016-00022)” the colleagues of the Department of Basic Technical Studies of the Faculty of Engineering of the University of Debrecen worked out workshops for secondary school students. One of the above mentioned workshops is the „Dynamics workshop supported by computer software”, the topic of which is the experimental and theoretical study of dynamic problems using highly developed computer software. Apart from describing the above mentioned workshop and the experiences related to it, we also present the reactions of the students, and describe how the workshop contributes to their widening knowledge.. Furthermore, we also analyse what knowledge, skills and information students would need to be more creative, motivated and initiative and this way more successful in their studies and at work, as well as in their everyday lives, in the field of engineering. In the end, as a conclusion, we make recommendations concerning further improvements of the workshop.